Evaluation of PRNP Expression Based on Genotypes and Alleles of Two Indel Loci in the Medulla Oblongata of Japanese Black and Japanese Brown Cattle - Msalya, George (Public Library of Science, 2011)
BACKGROUND: Prion protein (PrP) level plays the central role in bovine spongiform encephalopathy (BSE) susceptibility. Increasing the level of PrP decreases incubation period for this disease. Therefore, studying the expression of the cellular PrP or at least the messenger RNA might be used in selection for preventing the propagation of BSE and other prion diseases. Two insertion/deletion (indel) variations have been tentatively associated with susceptibility/resistance of cattle to classical BSE. METHODOLOGY/PRINCIPAL FINDINGS: We studied the expression of each genotype at the two indel sites in Japanese Black (JB) and Japanese Brown (JBr) cattle breeds by a standard curve method of real-time PCR. Five diplotypes subdivided into two categories were selected from each breed. The two cattle breeds were considered differently. Expression of PRNP was significantly (p<0.0001) greater in the homozygous deletion genotype at the 23-bp locus in JB breed. Compared to the homozygous genotypes, the expression of PRNP was significantly greater in the heterozygous genotype at the 12-bp locus in JB (p<0.0001) and in JBr (p = 0.0394) breeds. In addition, there was a statistical significance in the PRNP levels between the insertion and the deletion alleles of the 23-bp locus in JB (p = 0.0003) as well as in JBr (p = 0.0032). There was no significance in relation to sex, age, geographical location or due to their interactions (p>0.05). CONCLUSION: Our results suggest that the del/del genotype or at least its del allele may modulate the expression of PRNP at the 23-bp locus in the medulla oblongata of these cattle breeds.